2022
DOI: 10.3390/cells11030520
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Pathways Promote Oligodendrocyte Progenitor Cell Recruitment to the Injury Site in Adult Zebrafish Brain

Abstract: The oligodendrocyte progenitors (OPCs) are at the front of the glial reaction to the traumatic brain injury. However, regulatory pathways steering the OPC reaction as well as the role of reactive OPCs remain largely unknown. Here, we compared a long-lasting, exacerbated reaction of OPCs to the adult zebrafish brain injury with a timely restricted OPC activation to identify the specific molecular mechanisms regulating OPC reactivity and their contribution to regeneration. We demonstrated that the influx of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 118 publications
(202 reference statements)
0
13
1
Order By: Relevance
“…Surprisingly, we did not observe any difference between SW CTRL and SW INH conditions at 3 dpi. This observation contrasts with the findings from our study in zebrafish, in which inhibition of both pathways was found to alleviate reactive gliosis by decreasing the accumulation of oligodendrocytes and their proliferation 49 . This lack of concordance might be due to differences in the injury environment, and additional pathways involved in the accumulation and proliferation of OPCs in the mouse cerebral cortex and may reflect a possible difference between regeneration competent and regeneration incompetent species.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, we did not observe any difference between SW CTRL and SW INH conditions at 3 dpi. This observation contrasts with the findings from our study in zebrafish, in which inhibition of both pathways was found to alleviate reactive gliosis by decreasing the accumulation of oligodendrocytes and their proliferation 49 . This lack of concordance might be due to differences in the injury environment, and additional pathways involved in the accumulation and proliferation of OPCs in the mouse cerebral cortex and may reflect a possible difference between regeneration competent and regeneration incompetent species.…”
Section: Discussioncontrasting
confidence: 99%
“…Fig. 9g), and our recent findings that Cxcr3 and Tlr1/2 regulate OPC accumulation at injury site in the zebrafish brain 49 , we investigated the injury-induced transcriptional changes after interference with the Cxcr3 and Tlr1/2 pathways. We used the Cxcr3 antagonist NBI-74330 50 and the Tlr1/2 pathway inhibitor CU CPT 22 51 to interfere with the above-mentioned pathways, and performed scRNA-seq analysis at 3 dpi and 5 dpi (henceforth referred to as SW INH or 3/5 dpi_INH if distinct time points are indicated) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the forebrain and spinal cord, RGCs drive the repair process. Accordingly, dorsal forebrain stab injury leads to the activation of RGCs, in addition to oligodendrocyte precursor cells (OPCs), that serve to replenish lost neurons and oligodendrocytes, respectively ( Kroehne et al, 2011 ; Baumgart et al, 2012 ; Kishimoto et al, 2012 ; Barbosa et al, 2015 ; Sanchez-Gonzales et al, 2022 ). Most recently, transcriptomic analysis has provided insight regarding early proliferative signatures of RGCs and OPCs in the telencephalon and spinal cord after injury ( Tsata et al, 2020 ; Demirci et al, 2022 ; Sanchez-Gonzales et al, 2022 ), adding to our existing knowledge of the role of cxcr5 and Gata3 during neurorepair ( Kizil et al, 2012a ; 2012b ).…”
Section: Cell Intrinsic and Injury-induced Signals Regulate Adult Neu...mentioning
confidence: 99%
“…Accordingly, dorsal forebrain stab injury leads to the activation of RGCs, in addition to oligodendrocyte precursor cells (OPCs), that serve to replenish lost neurons and oligodendrocytes, respectively ( Kroehne et al, 2011 ; Baumgart et al, 2012 ; Kishimoto et al, 2012 ; Barbosa et al, 2015 ; Sanchez-Gonzales et al, 2022 ). Most recently, transcriptomic analysis has provided insight regarding early proliferative signatures of RGCs and OPCs in the telencephalon and spinal cord after injury ( Tsata et al, 2020 ; Demirci et al, 2022 ; Sanchez-Gonzales et al, 2022 ), adding to our existing knowledge of the role of cxcr5 and Gata3 during neurorepair ( Kizil et al, 2012a ; 2012b ). In the dorsal forebrain, genes regulating stem cell quiescence under homeostasis, such as mdka , have also recently been shown to continue to be expressed following brain injury in non-reactive, RGC populations, suggesting a potential mechanism to prevent NSPC pool exhaustion ( Lübke et al, 2022 ).…”
Section: Cell Intrinsic and Injury-induced Signals Regulate Adult Neu...mentioning
confidence: 99%